Controversies in circulating tumor cell count during therapy. (June 2013) - Raimondi, Cristina; Gradilone, Angela; Gazzaniga, Paola
Circulating tumor cells (CTCs) are a potential biomarker for prognosis and predictor for therapeutic response. Besides enumeration, the molecular portrait of CTCs holds promise to reveal new insights into the biology of cancer. Although CTCs may represent a liquid biopsy useful for selection of personalized treatments, to date, inconclusive clinical data support the utility of such information in terms of measurable benefit for the individual cancer patient. To finally move CTCs from translational research to the clinical setting and incorporate CTC count/characterization in routine oncological practice, we still need a definitive validation. This is a goal that will be hard to achieve, since tracing a molecular profile of CTCs is hampered by the extremely high heterogeneity of these cells.